Novel TiO2 nanotube arrays for photoelectrocatalysis application - Al-Shihabi Al-Ani, Athil Khairi J. (2021)
The fast-growing energy and environmental concerns have motivated many researchers to move their efforts towards more sustainable and environmentally friendly renewable energy sources, particularly sunlight. Photoelectrocatalysis is a widely accepted technique that has great potential to utilise sunlight to enable desirable chemical reactions with low environmental impacts. This technique can employ an abundant, affordable, non-toxic, and environmentally friendly stable semiconductor as the photocatalyst, such as TiO2 nanotube arrays (NTAs), to assist water electrolysis in producing a clean fuel under the illumination of solar light.